Interaction in the molten system Rb2O‐P2O5‐TiO2‐NiO. Crystal structure of the langbeinite‐related Rb2Ni0.5Ti1.5(PO4)3. Issue 7 (29th May 2015) - Strutynska, Nataliia Yu.; Bondarenko, Marina A.; Ogorodnyk, Ivan V.; Zatovsky, Igor V.; Slobodyanik, Nikolay S.; Baumer, Vyacheslav N.; Puzan, Anna N.
<x xml:space="preserve">Abstract</x> The crystallization of molten system Rb2O‐P2O5‐TiO‐NiO was investigated at molar ratios Rb/P=0.5‐1.3, Ti/P=0.15, Ti/Ni=1.0. The phosphates RbTi2(PO4)3, Rb2Ni0.5Ti1.5(PO4)3 and RbNiPO4 have been prepared and characterized. The new obtained phosphate Rb2Ni0.5Ti1.5(PO4)3 belongs to the langbeinite family (cubic system, space group P213, a = 9.9386(2)Å). Three‐dimensional framework of Rb2Ni0.5Ti1.5(PO4)3 is build up from mixed (Ni/Ti)O6‐octahedra and PO4‐tetrahedra. Rb cations are located in the closed cavities of the framework.